Sulphonamide inhibition studies of the β-carbonic anhydrase GsaCAβ present in the salmon platyhelminth parasite Gyrodactylus salaris - Ashok Aspatwar; Alessandro Bonardi; Heidi Aisala; Ksenia Zueva; Craig R Primmer; Jaakko Lumme; Seppo Parkkila; Claudiu T. Supuran (Taylor & Francis Group, 2023)
A β-class carbonic anhydrase (CA, EC 4.2.1.1) present in the genome of the Monogenean platyhelminth Gyrodactylus salaris, a fish parasite, GsaCAβ, has been investigated for its inhibitory effects with a panel of sulphonamides and sulfamates, some of which in clinical use. Several effective GsaCAβ inhibitors were identified, belonging to simple heterocyclic sulphonamides, the deacetylated precursors of acetazolamide and methazolamide (KIsof 81.9-139.7 nM). Many other simple benezene sulphonamides and clinically used agents, such as acetazolamide, methazolamide, ethoxzolamide, dorzolamide, benzolamide, sulthiame and hydrochlorothiazide showed inhibition constants <1 µM. The least effective GsaCAβ inhibitors were 4,6-disubstituted-1,3-benzene disulfonamides, with KIs in the range of 16.9-24.8 µM. Although no potent GsaCAβ-selective inhibitors were detected so far, this preliminary investigation may be helpful for better understanding the inhibition profile of this parasite enzyme and for the potential development of more effective and eventually parasite-selective inhibitors.